1992
DOI: 10.1161/01.str.23.9.1271
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhidrosis as a reflection of autonomic failure in patients with acute hemispheral brain infarction. An evaporimetric study.

Abstract: Background and Purpose: Sweating dysfunction is one of the most frequently encountered symptoms of autonomic failure but has received scant attention in patients with cerebrovascular diseases. Our purpose was to evaluate the prevalence, pathogenesis, and clinical correlates of sweating dysfunction in stroke.Methods: We studied sweating at baseline and after a heating stimulus in 53 patients with acute hemispheral brain infarction and in 40 healthy control subjects by using a quantitative evaporimetric method.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 14 publications
1
36
0
1
Order By: Relevance
“…Indeed, we have recently demonstrated that the lateralization of DTH responses was significantly correlated to alteration of sympathetic nerve traffic in early stroke [21]. In addition, Korpelainen et al [29] and Naver et al [30] recently demonstrated that acute hemispheral brain infarction leads to lateralization of sympathetic nerve traffic.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Indeed, we have recently demonstrated that the lateralization of DTH responses was significantly correlated to alteration of sympathetic nerve traffic in early stroke [21]. In addition, Korpelainen et al [29] and Naver et al [30] recently demonstrated that acute hemispheral brain infarction leads to lateralization of sympathetic nerve traffic.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, Korpelainen et al . [29] and Naver et al . [30] recently demonstrated that acute hemispheral brain infarction leads to lateralization of sympathetic nerve traffic.…”
Section: Discussionmentioning
confidence: 99%
“…In most of these studies, however, only nonquantitative methods for assessing the amount of sweating have been used. By using quantitative evaporimetric measurements, our group [65,66] established an asymmetric sweating pattern in the majority of hemispheric stroke patients (Fig. 2).…”
Section: Sweating Disordersmentioning
confidence: 99%
“…The phenomenon is probably caused by an interruption of the cortica] sympathoinhibitory input to the putative neural pathway that controls sweating on the contra]ateral side of the body [49,[64][65][66]. Although the course of the sympathetic sudomotor pathway descending from the hypothalamus is clear, little is known about the higher neural structures regulating sweating.…”
Section: Sweating Disordersmentioning
confidence: 99%
“…Une sudation gustative est constatée cependant aussi en pré-sence de neuropathie diabétique (compensatoire), de blessures des Corda tympani, après des infections par Herpes Zoster, dans les cé-phalées de cluster (Cluster-Headache) après «Neck-dissection» et excision des glandes submandibulaires. L'infarctus cérébral conduit à une hyperhidrose significative sur le côté parésique du corps [7]. Une maladie neurologique avec hyperhidrose généralisée est le syndrome de Rilay-Day ou la dysautonomie familiale.…”
Section: Hyperhidrose Primaire Et Secondaire -Hyperhidrose Localisée unclassified